Respuesta :

(m-n)^2 = m^2 - 2mn + n^2

(m-n)^2  = m^2 + n^2 - 2mn

Substitute m^2 + n^2 = 18 and mn=7

(m-n)^2 =18 - 2(7)

(m-n)^2 = 18 - 14

(m-n)^2  = 4

Answer:

(m - n)^2 = 4

Step-by-step explanation:

(m - n) ^2 = m^2 - 2mn + n^2 when (m-n)^2 is expanded using foil.

But m^2 + n^2 = 18         Given

mn = 7                             Given

(m - n)^2  = m^2 + n^2 - 2 mn  Substitute in the given values

(m -  n)^2= 18 - 2*7           Reduce

(m - n)^2 = 18 - 14             Combine

(m - n)^2 =  4                

ACCESS MORE